Towards Overcoming Millennial Classroom Barriers: Reflections from Engineering Students on Blended Teaching and Learning Innovations - Bladergroen, Moira Catherina; Basson, Anton; Blaine, Deborah (Critical Studies in Teaching and Learning, 2023)
A proposition for the use of a blended teaching and learning approach maintains that(a)ease of access and flexibility,(b)an increase in the degree of active learning, and (c) an improvement in learning experiences and learning outcomes for students are expected accomplishments to implementation success. In this paper, we present an analysis of how a blended teaching and learning approach influenced the experiences of engineering faculty students. Our empirical analysis found that a blended teaching and learning approach is students’ preferred teaching strategy, and traditional face-to-face teaching strategies alone are no longer sufficient for achieving success with new generation engineering students. Further, we show how the blended teaching and learning approach can enhance understanding of engineering knowledge and support students who would otherwise lag behind. We also show how active support from faculty management enhances the implementation subtleties and advance the development of a dynamic pedagogy. Our findings offer lecturers important insights into students’ preferences, as well a show lecturers can endorse and design a teaching and learning approach that is agile and adaptable, meeting the challenges of the environment in which they are working, which is similarly in endless flux